Sensitivity of piezoresistive pressure sensor with inner diaphragm - Chua, Kean Hong; Ismail, Noor Faezah; Md Yunus, Nurul Amziah; Ahmad, Desa (IEEE, 2017)
This paper emphasizes the optimization of piezoresistive pressure sensor. The proposed design is to implement inner diaphragm to increase the sensitivity of the sensor. Comparison between the original design and proposed design is made. The adjustment and performance of the proposed design are also discussed.